NKT cell adjuvant-based tumor vaccine for treatment of myc oncogene-driven mouse B-cell lymphoma - Mattarollo, Stephen R; West, Alison C; Steegh, Kim; Duret, Helene; Paget, Christophe; Martin, Ben; Matthews, Geoffrey M; Shortt, Jake; Chesi, Marta; Bergsagel, P Leif; Bots, Michael; Zuber, Johannes; et al. (Blood, 2012)
Immunomodulators are effective in controlling hematologic malignancy by initiating or reactivating host antitumor immunity to otherwise poorly immunogenic and immune suppressive cancers. We aimed to boost antitumor immunity in B-cell lymphoma by developing a tumor cell vaccine incorporating α-galactosylceramide (α-GalCer) that targets the immune adjuvant properties of NKT cells. In the Eμ-myc transgenic mouse model, single therapeutic vaccination of irradiated, α-GalCer-loaded autologous tumor cells was sufficient to significantly inhibit growth of established tumors and prolong survival. Vaccine-induced antilymphoma immunity required NKT cells, NK cells, and CD8 T cells, and early IL-12-dependent production of IFN-γ. CD4 T cells, gamma/delta T cells, and IL-18 were not critical. Vaccine treatment induced a large systemic spike of IFN-γ and transient peripheral expansion of both NKT cells and NK cells, the major sources of IFN-γ. Furthermore, this vaccine approach was assessed in several other hematopoietic tumor models and was also therapeutically effective against AML-ETO9a acute myeloid leukemia. Replacing α-GalCer with β-mannosylceramide resulted in prolonged protection against Eμ-myc lymphoma. Overall, our results demonstrate a potent immune adjuvant effect of NKT cell ligands in therapeutic anticancer vaccination against oncogene-driven lymphomas, and this work supports clinical investigation of NKT cell-based immunotherapy in patients with hematologic malignancies.